Resonant excitation of plasma waves in a plasma channel - Ross, AJ; Chappell, J; van de Wetering, JJ; Cowley, J; Archer, E; Bourgeois, N; Corner, L; Emerson, DR; Feder, L; Gu, XJ; Jakobsson, O; Jones, H; et al. (American Physical Society, 2024)
We demonstrate resonant excitation of a plasma wave by a train of short laser pulses guided in a preformed plasma channel, for parameters relevant to a plasma-modulated plasma accelerator (P-MoPA). We show experimentally that a train of N≈10 short pulses, of total energy ∼1J, can be guided through 110mm long plasma channels with on-axis densities in the range 1017-1018cm-3. The spectrum of the transmitted train is found to be strongly red shifted when the plasma period is tuned to the intratrain pulse spacing. Numerical simulations are found to be in excellent agreement with the measurements and indicate that the resonantly excited plasma waves have an amplitude in the range 3-10GVm-1, corresponding to an accelerator stage energy gain of order 1GeV.